A comprehensive roadmap for MedTech innovations uptake into the public healthcare system in India - Gupta, Prakamya; Rai, Charu; Shahi, Anjaney; Sharma, Manisha; Choudhury, Ranjan; Kotwal, Atul (Frontiers in Digital Health, 2023)
The burden of communicable, non-communicable diseases and reproductive maternal, newborn, child & adolescent health in India, reflects the necessity to develop tailored solutions. The plethora of MedTech innovations has provided healthcare facilities with more effective, affordable and accessible for people across the country. However, in spite of the Make-in-India scheme in the country, the indigenously developed healthcare technology are far from making an impact on the healthcare system Objective: To present a roadmap for MedTech innovations for their successful deployment into the public healthcare system Methodology: In addition to the literature review, recommendations were included from several stakeholders such as innovators, manufacturers, policymakers, subject matter experts, funding organisations, State health officials etc.The journey of healthcare innovation from need identification to ideation, to prototyping and validation has paved the way towards the de novo design that caters to unmet needs. Innovations at the advanced technology readiness level (TRL 7/8 and above) demand a holistic and multidisciplinary approach which includes clinical validation, regulatory approval and Health technology assessment. The deployment of healthcare technology into the public healthcare system must consider resources (e.g., time, staff, budget, investment policies), ethical concerns (privacy, security, regulations, ownership), governance (policy, accountability, responsibility etc.), and Skills (capabilities, culture, etc.). The technologies are considered for field trials before the uptake in the public health system. Technology can be a key tool in achieving Universal Health Coverage but its use has to be strategic, judicious, and cognizant of issues around privacy and patient rights.